Electronic Negotiable Warehouse Receipt (eNWR): A Tool to Promote Liquidity in Rural Area - Bhagwat, Kanchan; Angadi, Sangamesh; Vashisth, Akshita; Shalendra, (Journal of Agricultural Extension Management, 2024)
The warehouse receipt serves as collateral for loans, for delivery in accordance with a futures contract or for swapping. Realising the importance, the Government has taken various initiatives to make warehouse receipt negotiable, transparent and a sound instrument facilitating trade transactions and availability of credit mainly to smallholder farmers. Introduction of repositories have facilitated the introduction of a true electronic warehouse receipt in the Country. The electronic receipt exhibit various advantages over paper receipts. The system having online centralised management of records is transparent, efficient and facilitates easy transfer and splitting of receipts. Nearly one lakh electronic receipts were issued during 2020-21 by both the repositories namely NeRL and CCRL. The electronic warehouse receipt has shown its potential, though, it may need consumer specific products and creation of awareness to make the same popular among farmers.